Labrador, aerial view of coastal mountains and inlets between Ungava Bay and Nachvak Fjord - Forbes, Alexander, 1882-1965 (1931)
(Series 34) West-east flight from Ungava Bay to Nachvak. Camera facing right front to line of flight. Grayscale